2019
DOI: 10.1038/s41467-019-09372-x
|View full text |Cite
|
Sign up to set email alerts
|

Humidity-tolerant rate-dependent capillary viscous adhesion of bee-collected pollen fluids

Abstract: We report a two-phase adhesive fluid recovered from pollen, which displays remarkable rate tunability and humidity stabilization at microscopic and macroscopic scales. These natural materials provide a previously-unknown model for bioinspired humidity-stable and dynamically-tunable adhesive materials. In particular, two immiscible liquid phases are identified in bioadhesive fluid extracted from dandelion pollen taken from honey bees: a sugary adhesive aqueous phase similar to bee nectar and an oily phase consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…The mutualistic relationship between plants and honey bees results from the exchange of nectar and pollen. Bees play a vital role in the pollination of plants [40], and plants secrete a rich liquid sugar similar to nectar from their glands to attract pollinators to their flowers so that the pollen can adhere to bee-collected pollen grains [42]. Researchers have found that honey bees (A. mellifera L.) appear to prefer crops rich with nectar and pollen in order to store large quantities of food, thus sustaining the colony growth and improving foraging performance [43,44].…”
Section: Honey Beesmentioning
confidence: 99%
“…The mutualistic relationship between plants and honey bees results from the exchange of nectar and pollen. Bees play a vital role in the pollination of plants [40], and plants secrete a rich liquid sugar similar to nectar from their glands to attract pollinators to their flowers so that the pollen can adhere to bee-collected pollen grains [42]. Researchers have found that honey bees (A. mellifera L.) appear to prefer crops rich with nectar and pollen in order to store large quantities of food, thus sustaining the colony growth and improving foraging performance [43,44].…”
Section: Honey Beesmentioning
confidence: 99%
“…They could also use adhesion tests with varying approach speeds to measure the pollen pellet's adhesion energy with the corbicula, such as with an AFM. Such techniques have previously been used for measuring pollen adhesion [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“… common name species family glue function Ref. barley hordeum vulgare poaceae attachment with hulls [ 47 ] chia salvia hispanica lamiaceae protection of germ [ 48 ] orchid phalaenopsis aphrodite orchidaceae pollen spreading [ 49 ] philodendron syngonium podophyllum araceae attachment [ 50 ] arabidopsis arabidopsis thaliana brassicales germination [ 51 ] tropical milkweed asclepias curassavica apocynaceae pollen spreading [ 52 ] dandelion taraxacum officinale asteraceae pollen spreading [ 53 ] fly bush roridula gorgonias roridulaceae prey capture [ 54 , 55 ] sundew drosera capensis drosera glanduligera drosophyllum lusitanicum droseraceae drosophyllaceae prey capture [ 42 , 56 , 57 ] ivy hedera helix parthenocissus tricuspidate araliaceae vitaceae attachment [ 37 , 38 ] aloe vera aloe barbadensis Miller asphodelaceae storage, protection from desiccation [...…”
Section: Naturally Occurring ‘Sticky’ Compounds Originating From Animal and Plant Sourcesmentioning
confidence: 99%